PWE-137 The prevalence of anaemia in coeliac disease, and the demand in this group for intra-venous iron therapy. (17th June 2017) - Johnson, LB; Sakthivel, GD; Rostami, K; Marsh, MN; Johnson, MW
Abstract : Introduction: The current prevalence of Coeliac Disease (CD) in UK is said to be around 1 per 100 (1%) individuals[1, 2]. For the last 10 years there has been a regional drive from our CCG to discharge confirmed coeliac patients back to their GPs for community based care. It often seems that we see these patients later on in their disease course, with complications that were potentially avoidable. Iron deficiency anaemia (IDA) is a common problem in CD, and is said to occur with a prevalence as high as 46% [1], whilst up to 8.7% of all unexplained IDA appears to be associated with CD [2]. Objective: To assess the prevalence of IDA in our CD cohort, and the recurrence of IDA in these patients over a 7 year period. In those failing to correct (eg. with oral iron), we aimed to review the proportion that received intravenous (IV) iron. Method: The Luton and Dunstable University Hospital serves a catchment of 3 30 000 and has a CD database of 1430 patients (0.43%), which is slightly lower than the 1% National prevalence rate. Over the last 7 years we have compiled a database documenting each occasion a patient has presented for blood tests and has had evidence of confirmed IDA. For the purposes of this study we defined iron deficiency anaemia as a haemoglobin level of <13 g/L for men and <12 g/L for women, in the presence of a ferritin of <50 ng/ml. The two databases were compared. The number of presentations with IDA over that 7 year period was assessed, along with the demand for IV iron. Results: Coeliac disease was found to be associated with 1.7% (967/54977) of all the IDA picked up over the 7 year review period. Conversely, 420 (or 29%) of our 1430 local CD patients were found to have IDA. 388 CD patients presented 967 times with IDA (an average of 2.5 times each, range 1–35 times). Of these 420 CD patients with IDA, just 4% (17/420) received an IV iron infusion. Conclusion: Over a 7 year review period 29% of our CD cohort were found to have IDA. Despite tiredness and lethargy being the most common symptom CD patients complain of impacting on their daily lives, just 4% of these received IV iron supplementation. Many of these patients had presented on multiple occasions with IDA (average 2.5 times). Due to the previous CCG drive to discharge these patients back to their GPs for community based follow up, it is possible that these results show a failure in the community monitoring and management system. References: . Bottaro G, Cataldo F, Rotolo N, Spina M, Corazza GR. The clinical pattern of subclinical/silent celiac disease: an analysis on 1026 consecutive cases. Am J Gastroenterol 1999; 94:691–696. . Hematologic manifestations of celiac disease. Thorvardur R. Halfdanarson, Mark R. Litzow and Joseph A. Murray. Blood 2007 109:412–421. Disclosure of Interest: None Declared